Hydraulic systems control based on the characteristics of major-motion mechanism for an open-die forging manipulator. (February 2017) - Hou, Jiaoyi; Zhang, Zengmeng; Zhou, Hua; Ning, Dayong; Gong, Yongjun
In the open-die forging process, the forging manipulator must cooperate closely with the forging press. Terrible working conditions of open-die forging have resulted in significant demand on the hydraulic control systems of the forging manipulator. This article analyzes the characteristics of major-motion hydraulic systems with the aim of proposing a novel hybrid serial–parallel heavy-duty forging manipulator. Kinematic and dynamic models of the major-motion mechanism are developed to investigate the control and comply with performance of hydraulic lifting, pitching, and buffering systems. Simulation shows that the three hydraulic systems are coupled in the position and posture control of the clamp. A separate posture control method based on the characteristic of the major-motion mechanism is designed for the hydraulic systems, and the position tracking performance of the hydraulic systems is studied in a stretching process of a plat-tool.